2019
DOI: 10.21705/mcbs.v3i2.66
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and Its Role in Inflammatory Process of Obesity

Abstract: Obesity is a chronic, low degree systemic inflammatory status. Microarray examination shows a disturbance in the expression of cytokine, chemokine, complementary protein and half of the other acute phase components in obese patients. Adiponectin is the hormone that increases insulin sensitivity, while its level decreases under condition of fatty tissue enlargement that occurs in obesity. Excessive weight causes the adipocyte cells and adipose tissues produce various types of mediators. The inflammatory process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The adipocytokines secreted by the adipocytes including adiponectin, leptin, TNF-α, resistin and plasminogen activator 1 (PAI-1) control appetite, insulin sensitivity and inflammation; hence, they play their role in the MAFLD’s pathogenesis and its development to NASH [ 25 ]. An elevation in adiponectin level has been connected with the inhibitions of hepatic lipid accumulation and insulin resistance as well as exerting its hepatoprotective actions by reducing the production of pro-inflammatory cytokines and increasing the expressions of anti-inflammatory IL-10 and IL-1 receptor antagonists [ 68 , 69 ]. This study also demonstrated a marked decrease in the level of serum adiponectin in the HFD group compared with the NC group.…”
Section: Discussionmentioning
confidence: 99%
“…The adipocytokines secreted by the adipocytes including adiponectin, leptin, TNF-α, resistin and plasminogen activator 1 (PAI-1) control appetite, insulin sensitivity and inflammation; hence, they play their role in the MAFLD’s pathogenesis and its development to NASH [ 25 ]. An elevation in adiponectin level has been connected with the inhibitions of hepatic lipid accumulation and insulin resistance as well as exerting its hepatoprotective actions by reducing the production of pro-inflammatory cytokines and increasing the expressions of anti-inflammatory IL-10 and IL-1 receptor antagonists [ 68 , 69 ]. This study also demonstrated a marked decrease in the level of serum adiponectin in the HFD group compared with the NC group.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence and health impacts of obesity-related diseases are on the rise, doubling in more than 70 countries between the years of 1980 and 2015, and global estimates indicate that 604 million adults are obese [ 1 ]. Obesity is associated with immune responses that lead to a systemic low-grade proinflammatory state derived from an increase in adipocytes, loss of balance with immune cells, and the release of cytokines such as interleukin 6 (IL-6), which decreases adiponectin secretion [ 2 , 3 ]. In obesity, the IL-6 concentration increases, which decreases the sensitivity to insulin and increases glucose absorption in peripheral tissues [ 4 , 5 , 6 ], causing metabolic and cardiovascular diseases [ 7 ] and diabetes mellitus 2 [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that reducing TC, TG, and LDL levels can effectively alleviate NAFLD [ 24 ]. Adiponectin is a cytokine expressed and secreted by adipose tissue and that exerts anti-inflammatory effects, increases fatty acid β-oxidation, and reduces lipid accumulation in liver cells [ 25 ]. In the present study, we found that AGL9 administration substantially decreased adiponectin levels and rescued the NAFLD phenotype, suggesting its potential as a treatment strategy for lipid-metabolism disorders.…”
Section: Discussionmentioning
confidence: 99%